Nilai Moral Dalam Novel Tanah Baru Tanah Air Kedua Kajian Struktural Genetik - Yuli Kurniasih (UHAMKA Graduate School Thesis Abstract Collection, 2016)
This aims of the Thesis is to know and to analyze the moral volues in Tanah Baru Tanah Air Kedua (The New Land The Seond Homland) novel by N.H Dini. The methods used in the research is Qualitative Desriftive Menthos content analysis by using Structural Studies of Genetik. The objet of the research is Tanah Baru Tanah Air Kedua (The New Land The Seond Homland) novel by N.H Dini. The fous of this research is the intrinsic elemen novel related with moral volue of Tanah Baru Tanah Air Kedua (The New Land The Seond Homland) novel by N.H Dini. The rearch imstrumen is the researchers assisted by analysis tables. Data analysis was reading Tanah baru Tanah Air Kedua by N.H Dini, the moral volues in Tanah Baru Tanah Air Kedua (The New Land The Seond Homland), included the results pf the analysis and concluded the results of analysis. The moral volues were analyzed in this research are : (1) the honesty, (2) the willingness to take responsibility, (3) the independence, (4) the courage, (5) the mondesty, (6) the religius. The result of the research obtained from the data analysis on novel by N.H Dini was the most promainent moral volue is the modesty though figures Samirin. It was reasonable beause according to the situation and conditions in the tranmigraton program. The situation and conditions in the tranmigraton program to have moral volues humility in order to live in peace and prosperity. This aresearch has implication for the study of literature in high schools, particulary on the intrinsic elements of characters Samirin in the novel, to broaden and improve the ability of students to the appreciation of literature, especially novel Tanah Baru Tanah Air Kedua (The New Land The Seond Homland) novel by N.H Dini.